Abelia x grandiflora: Glossy Abelia - Edward F. Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This 3-page Shrub Fact Sheet that discusses Abelia grandiflora is a minor revision. Written by Edward F. Gilman, Ryan W. Klein, and Gail Hansen, and published by the Environmental Horticulture Department, November 2017.